Collaborating for the Successful Retirement and End-of-Life Care of Non-Human Primates in Biomedical Research - Amanda R. Maxwell; Eric K. Hutchinson; Jaclyn V. Allen; Melissa C. Painter; Lydia M. Hopper (Veterinary Sciences)
Research facilities have established animal adoption programs for laboratory animals. However, adoption to private owners is not an option for non-human primates (NHPs), so their post-research life presents a unique challenge. Here, we describe a collaborative effort between laboratory animal veterinarians and behavioral management staff in retiring NHPs in place to ensure their quality of life after the completion of research projects. The success of our retirement program hinges on our collaborative efforts to manage clinical diseases such as arthritis, amyloidosis, and diarrhea; to surgically ex-plant previous research hardware; and to evaluate the animals’ behavior and temperament to ensure each individual is placed in a new group or living situation in which they are likely to be successful and to have good welfare. Implementation of a quality-of-life assessment tool for all retired animals allows all staff involved in the animals’ care to proactively and periodically assess the quality of life of these animals. The successful retirement of NHPs living in social groups is rewarding for all personnel and promotes a culture of caring. Research animal retirement is an important way for us to give back and honor the contributions these animals have made to advancing medicine.